Decision-Making Analysis for Allergen Immunotherapy versus Nasal Steroids in the Treatment of Nasal Steroid–Responsive Allergic Rhinitis. Issue 1 (January 2014) - Kennedy, Joshua L.; Robinson, Derek; Christophel, Jared; Borish, Larry; Payne, Spencer
Background: The purpose of the study was to determine the age at which initiation of specific subcutaneous immunotherapy (SCIT) becomes more cost-effective than continued lifetime intranasal steroid (NS) therapy in the treatment of allergic rhinitis, with the use of a decision analysis model. Methods: A Markov decision analysis model was created for this study. Economic analyses were performed to identify "break-even" points in the treatment of allergic rhinitis with the use of SCIT and NS. Efficacy rates for therapy and cost data were collected from the published literature. Models in which there was only incomplete improvement while receiving SCIT were also evaluated for economic break-even points. The primary perspective of the study was societal. Results: Multiple break-even point curves were obtained corresponding to various clinical scenarios. For patients with seasonal allergic rhinitis requiring NS (i.e., fluticasone) 6 months per year, the age at which initiation of SCIT provides long-term direct cost advantage is less than 41 years. For patients with perennial rhinitis symptoms requiring year-round NS, the cut-off age for SCIT cost-effectiveness increases to 60 years. Hypothetical subjects who require continued NS treatment (50% reduction of previous dosage) while receiving SCIT also display break-even points, whereby it is economically advantageous to consider allergy referral and SCIT, dependent on the cost of the NS prescribed. Conclusion: The age at which SCIT provides economic advantages over NS in the treatment of allergic rhinitis depends on multiple clinical factors. Decision analysis models can assist the physician in accounting for these factors and customize patient counseling with regard to treatment options.